Impact of salinity on Streptococcus agalactiae and health parameters of Oreochromis niloticus during streptococcosis outbreaks - Rajan Preenanka; Muhammed P. Safeena; Basura Vidhya; TG Sumithra (The Microbe)
S. agalactiae infection is one of the most important bacterial diseases imparting mass mortality in the aquaculture sector, worldwide. It is responsible for posing both economic burdens and risks of cross-infectivity and zoonotic transmission. In this aspect, this study examined the virulence gene profiles, molecular serotyping and pathogenicity of S. agalactiae strains isolated from tilapia farms in Kerala, India in 2022. Following sample collection and processing, three S. agalactiae strains (KSA/01, KSA/02, and KSA/03) were isolated and confirmed the bacterial identity using 16S rRNA sequencing. In pathogenicity test, the LD50 of the S. agalactiae was found to be 1 × 106 CFU/ml. An increase in the salinity was found to affect the pathogenicity of S. agalactiae as well as the hematological and serological profile of tilapia. Thus the presence of S. agalactiae, a highly virulent and zoonotic pathogen in tilapia farms, underscores the imperative of continuous monitoring in aquaculture facilities.